Long-term radiographic appearance of calcium-phosphate synthetic bone grafts after surgical treatment of tibial plateau fractures. Issue 12 (December 2017) - Hanke, Alexander; Bäumlein, Martin; Lang, Siegmund; Gueorguiev, Boyko; Nerlich, Michael; Perren, Thomas; Rillmann, Paavo; Ryf, Christian; Miclau, Theodore; Loibl, Markus
Abstract: Objectives: Synthetic bone grafts (SBGs) are widely used to fill bone defects after fracture reduction. This study assessed the long-term resorption of two different calcium phosphate products (A = ChronOS™ inject and B = Norian ® SRS ® ; both DePuy Synthes, Oberdorf, Switzerland) used in the surgical treatment of tibial plateau fractures. Design: Long-term clinical and radiologic follow-up of 52 patients after surgical treatment of intraarticular tibial plateau fractures augmented with SBGs. Setting: The study was performed at a level 3 trauma center. Patients: Between January 2000 and December 2006 a total of 52 patients with intraarticular tibial plateau fractures were operatively treated and augmented with SBGs consisting of a Brushite matix with β-TCP granules (SBG A) or hydroxylapatite with 4–6% carbonate content (SBG B). 46 patients could be contacted and 38 were included in the study. Half of the patients received SBG A and the other half SBG B. Main outcome measurements: Loss of reduction and SBG resorption was investigated by comparison of follow-up X-ray images to pre- and postoperative X-ray images. Furthermore, pain, activity level and knee function were evaluated by means of questionnaires and clinical examination. Results: The mean age of patients was 59.7 ± 12.5 years. The follow-up was 8.6 ± 0.9 years for SBG A and 11.6 ± 1.4 years for SBG B (p < 0.001). In most cases SBG A was completely resorbed in a homogenous pattern, while SBG B was still visible on the X-ray images revealing a peripheral resorption pattern. A loss of reduction (>2 mm) could be observed in two patients with SBG A and two patients with SBG B, although only one of them had an impaired knee function. Conclusions: The composite SBG A reveals a comprehensive long-term resorption in comparison to SBG B. Nevertheless, both provided suitable mechanical support as part of the surgical treatment of tibial plateau fractures. Level of evidence: Case series, Level IV.